Dampak Investasi Dan Tenaga Kerja Asing Terhadap Kesempatan Kerja Tenaga Kerja Asal Indonesia - Ari Yuliastuti (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2018)
Foreign investment (PMA) and foreign workers (TKA) become an inseparable issue in a country's economic liberalization. Many theories argue that PMA and TKA will have a negative impact on the workforce of the investment destination country if the human resources and policies in the country are not ready. The objective of this paper is to examine the impact of investment, especially foreign investment and the number offoreign workers to employment opportunities for workers from Indonesia. The data used comes from the Directorate of Foreign Workers Use Control, the Ministry of Manpower, the Investment Coordinating Board (BKPM) and the Central Bureau of Statistics (BPS). This paper usesdescriptive qualitative analysis because of the limitations of available data. The analysis shows that the number of PMA has a positive impact on the number of foreign workers entering Indonesia, where the dominance of foreign workers from China has increased in the last five years. From this increasing number of foreign workers is not seen to make the Indonesian workforce increasingly urged. Indonesia's labor force tends to stagnate and even the number of unemployed also declines.